The case of international student enrollment and ethnic migration to Kosovo: Examining the geography of academic outcomes - Rader, Cassie L. B.; Katsumoto, Shinji; Stroup, Nicholas R.; Hall-Martin, Molly E.; Louie, Gordon; Fender, Celine D. (Journal of International Students, 2026)
Approximately 8% of students in the Republic of Kosovo’s public universities bachelor’s-level study programs are international students. As a young nation (Kosovo declared independence in 2008), and one with weak higher education coordination, domestic and international accreditation challenges, and persistent political influence in university affairs, these structural conditions do not necessarily inspire international student enrollment. Nevertheless, with a consistent flow of international students entering programs in Kosovo, we ask: What are the characteristics of international students who are enrolling in Kosovo’s public universities? And, how do Kosovo’s international students fare academically? – Is their relative success shaped by their country of origin? Using a longitudinal sample of 69,867 students starting from 2012 (the earliest available data on Kosovo’s public higher education following adoption of the Law on Higher Education in 2011), we describe patterns of international students, and use blocked logistic regression to model their success, and relative failure.